PENGOPERASIAN SHUTTER DAN PANCING CUMI IRADIUM PADA PENANGKAPAN UMPAN HANDLINE TUNA UNTUK KEBERLANJUTAN - Hendra Poltak; Misbah Sururi; Sudirman Sudirman; Muhammad Ali Ulat; Abudarda Razak; Muh Kasim (Buletin SWIMP, 2021)
handline is an environmentally friendly and low-cost fishing gear. This fishing gear can be modified so that it can reduce the operational and environmental impact of service partners as many as 10 people are representatives of handline fishermen, Pulau Raam Village. The material given is in the form of understanding sustainable fisheries, shutter fishing, and iradium squid fishing. Evaluation of the results of socialization by conducting question and answer interactions was obtained. Most of them understood the material given.